2022
DOI: 10.3389/fmed.2022.721119
|View full text |Cite
|
Sign up to set email alerts
|

Periodontitis and Subsequent Risk of Cataract: Results From Real-World Practice

Abstract: BackgroundPeriodontitis can lead to systemic inflammation and oxidative stress, contributing to the development of various diseases. Periodontitis could also be associated with several ocular diseases.MethodsWe conducted a retrospective population-based cohort study using the National Health Insurance Research Database of Taiwan to evaluate the risk of cataract in people with and without periodontitis. We established a periodontitis cohort and a non-periodontitis cohort, which included 359,254 individuals betw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 29 publications
0
3
0
Order By: Relevance
“…Moreover, limited evidence supports the effect of periodontitis or oral hygiene on cataract occurrence. In a retrospective study that evaluated the risk for cataract in subjects with and without periodontitis by referring to the national health insurance research database of Taiwan, subjects with periodontitis have a higher risk for cataract development than those without periodontitis ( 29 ). Considering these previous and our research results, our findings were meaningful because they showed that tooth loss, frequent tooth brushing, and dental scaling were associated with the risk of cataract occurrence.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, limited evidence supports the effect of periodontitis or oral hygiene on cataract occurrence. In a retrospective study that evaluated the risk for cataract in subjects with and without periodontitis by referring to the national health insurance research database of Taiwan, subjects with periodontitis have a higher risk for cataract development than those without periodontitis ( 29 ). Considering these previous and our research results, our findings were meaningful because they showed that tooth loss, frequent tooth brushing, and dental scaling were associated with the risk of cataract occurrence.…”
Section: Discussionmentioning
confidence: 99%
“…Periodontitis is an inflammation of gingival tissue that is characterized by microbial dysbiosis in the oral cavity and a subsequent loss of periodontal ligament attachment and alveolar bone [ 51 , 66 ]. Due to the shared risk factors between periodontitis and various ocular diseases, periodontitis has been shown to be correlated with an increased risk of developing primary open-angle glaucoma [ 67 ], cataracts [ 68 , 69 ], scleritis [ 70 ], and age-related macular degeneration [ 71 , 72 ]. Non-SEs have exhibited both pro-inflammatory and immunoprotective effects in periodontitis [ 73 , 74 ].…”
Section: Exosomes In Non-ocular Diseasesmentioning
confidence: 99%
“…Periodontitis causes systemic inflammation and oxidative stress, which can lead to a number of diseases ( Kurek-Gorecka et al, 2022 ; Xu et al, 2022 ; Yeh et al, 2022 ). Bacteria in inflamed gingival tissue and virulence factors are capable of entering the bloodstream to induce systemic inflammatory response, thus influencing the pathological process of many diseases, such as cardiovascular diseases, diabetes, chronic kidney disease, as well as liver injury.…”
Section: Periodontitis and Systemic Diseases Interrelationships: Role...mentioning
confidence: 99%